Prime ministers and party governments in Central and Eastern Europe. Issue 3 (3rd July 2021) - Grotz, Florian; Kukec, Marko
ABSTRACT: This article is the introduction to a special issue on Prime Ministers (PMs) and party governments in Central and Eastern Europe (CEE). It argues that the political survival of PMs in post-communist democracies depends on their interrelationships with other actors in three different arenas. The first arena encompasses the linkages between PMs and their parties. In this respect, being a party leader is a major power resource for PMs to retain their office even under critical circumstances. At the heart of the second arena is the PMs' relationship to other parliamentary parties. In this regard, the high fragmentation and fluidity of many post-communist party systems pose enormous challenges for PMs to secure constant parliamentary support. In the third arena, PMs are confronted with state presidents. Relatively strong CEE presidents, especially in semi-presidential systems, may use their constitutional powers to interfere in the political domain of PMs and thus jeopardise the stability of party governments. For each of these interrelationships, the article provides systematic evidence for eleven CEE democracies from 1990 to 2019 and situates the findings of the volume's contributions within a broader comparative perspective.